Perioperative patient-controlled regional analgesia versus patient-controlled intravenous analgesia for patients with critical limb ischaemia: a study protocol for a randomised controlled trial - Yuguang Huang; Yuehong Zheng; Yuelun Zhang; Jiao Zhang; Si Chen; Zhonghuang Xu; Hongju Liu; Yuexin Chen (BMJ Open)
Introduction Both regional analgesia and intravenous analgesia are frequently used perioperatively for patients with critical limb ischaemia (CLI). Nevertheless, the comparison of perioperative effect of regional and intravenous analgesia has not yet been thoroughly illustrated. This study will comprehensively compare patient-controlled regional analgesia (PCRA) and patient-controlled intravenous analgesia (PCIA) as two different perioperative analgesia approaches for patients with CLI. It investigates their effects on analgesia, reperfusion and the quality of recovery perioperatively, also aims to provide clinical evidence to those non-surgical patients with non-reconstructable arteries.Methods and analysis This trial is a randomised, single-centre, open-label, parallel trial with target sample size of 52 in total. Eligible participants will be randomly allocated to the PCRA group (group R) or the PCIA group (group I) after admission. Participants in group R will receive ultrasound-guided subgluteal sciatic catheterisation, followed by continuous PCRA infusion (0.2% ropivacaine 15 mL as loading dose, 8 mL/hour as background with a patient-controlled bolus of 6 mL). Participants in group I will receive PCIA (morphine is given in boluses of 1 mg as needed, background infusion at 1 mg/hour). Data will be collected at baseline (T0), 2 hours before revascularisation treatment (T1) and 2 hours before discharge (T2). The primary outcomes include the Numerical Rating Scale pain score at T1 and T2. The secondary outcomes include the perioperative transcutaneous oxygen pressure, the Tissue Haemoglobin Index, Hospital Anxiety and Depression Scale at T1 and T2; the Patient Global Impression of Change and patient satisfaction at T1 and T2; the perioperative cumulative morphine consumption, the length of postoperative hospital stay and adverse events.Ethics and dissemination This study received authorisation from the Institutional Review Board of Peking Union Medical College Hospital on 21 March 2017 (approval no. ZS-1289X). Study findings will be disseminated through presentations at scientific conferences or publications in peer-reviewed journals.Trial registration number Chinese Clinical Trial Registry (ChiCTR2000029298).Protocol version V.4CP.B2 (15 June 2020).